1955
DOI: 10.1084/jem.101.4.367
|View full text |Cite
|
Sign up to set email alerts
|

Specific Agglutination of Treponema Pallidum by Sera From Rabbits and Human Beings With Treponemal Infections

Abstract: For many years it was suspected that a specific immune response develops in the course of infection with Treponema pallidum, but despite attempts by many investigators to demonstrate specific antibodies, only recently have such efforts been successful. Work on this problem led to the discovery of the Wassermann reaction which together with its various modifications that employ lipoid antigens has been found to have a high degree of accuracy in the detection of syphilitic and related infections. However, it is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
2

Year Published

1957
1957
1981
1981

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(13 citation statements)
references
References 16 publications
0
11
0
2
Order By: Relevance
“…We have recently reevaluated, and slightly modified, an isolation procedure devised some years ago for preparing T. pallidum suspensions for immune agglutination (5). The findings presented here show that treponeme suspensions with high yields of apparently clean organisms can be recovered regularly.…”
mentioning
confidence: 90%
“…We have recently reevaluated, and slightly modified, an isolation procedure devised some years ago for preparing T. pallidum suspensions for immune agglutination (5). The findings presented here show that treponeme suspensions with high yields of apparently clean organisms can be recovered regularly.…”
mentioning
confidence: 90%
“…Des n o m b re u x tra v a u x p récem m en t consacrés à ces réactio n s ( T a n i [4 7 ,4 8 ], Cain [49], H a rd y et N ell [50], M cLeod et M agnuson [51], E h rm a n n et N ielsen [52], B ekker [53], K ilra y [54], etc.) il resso rt que les m éth o d es proposées c o m p o rte n t de nom breuses différences p o rta n t su r la souche de T P utilisée com m e an tig èn e, le tr a ite m e n t des lapins a v a n t l 'in o c u la tio n , le liq u id e d 'e x tra c tio n des T P , la m éth o d e d 'in a c tiv a tio n , l'a g e n t c o n serv ateu r, le v o lum e des réactifs, la co n c e n tra tio n m a x im u m d u séru m e t la d u rée de la période d 'in c u b a tio n ; il est donc difficile de co m p a re r e n tre eu x les ré s u lta ts o b ten u s ainsi dans des co n d itio n s fo rt différentes.…”
Section: Les Réactions D'agglutination Des Tréponèmes Pâlesunclassified
“…M cLeod et Stokes [55] o n t p u m o n tre r que les sérum s sy p h ilitiques c o n te n a ie n t au m oins d eu x a n tic o rp s a g g lu tin a n ts les tréponèm es p âles; l'u n d 'eu x , q u i p ro v o q u e une a g g lu tin a tio n ra p id e a p u être identifié à la réag in e de W a sse rm a n n ; H ardy et N ell [50] o n t pensé p o u v o ir su p p rim e r c e tte actio n a g g lu tin an te de la réagine en p ra ti q u a n t a v a n t la ré a c tio n d 'a g g lu tin a tio n une ab so rp tio n d u séru m par l'an tig èn e d u V D R L ; m ais c e tte m an ip u latio n se ra it in su ffisan te à en croire M agnuson et M cLeod [56].…”
Section: Les Réactions D'agglutination Des Tréponèmes Pâlesunclassified
“…Researchers working in syphilis research have also reported using an agglutination test for diagnosis of specific T. pallidum antigens (McLeod and Magnuson, 1953;Hardy and Nell, 1955).…”
Section: Discussionmentioning
confidence: 99%
“…They found that such suspensions gave specific agglutination reactions with T. pallidum-antisera when fresh bovine serum was present in the test mixture. Hardy and Nell (1955) developed an agglutination technique which in volved adsorbing out nonspecific agglutinins from sera with cardiolipin lecithin-cholesterol antigen (VDRL antigen). This enabled the authors to show a specific reaction between treponeme agglutinins and treponeme antigens.…”
Section: Serology Of Treponemesmentioning
confidence: 99%